Effect of Temporal Filters on Face Images - Ihsan, Rasheed Rebar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Face detection from low-resolution videos is a challenging research area. This thesis explores the effect of a temporal filtering method by Dr. Bodur on face images. The temporal mean and median filters calculate the intensity of pixels using the intensities of surrounding neighbour pixels, and temporal neighbour pixels in consecutive images. The effect of the proposed technique on the image is measured by the mean square error (MSE) and the peak signal noise ratio (PSNR) values using the pixels of the original high resolution image as reference values to measure the error and noise figures of the pixels of filtered low resolution images. Results demonstrate a significant effect of the proposed filters on the consecutıve frames of face vıdeo record. In the tests, the medıan fılter ıs found more effective compared to mean fılter. Keywords: Temporal Mean Filter, Temporal Median Filter, Image Resolution, Effectiveness of Image Filter.

ÖZ: Düşük çözünürlüklü videolardan yüz tanıma zorlu bir araştırma alanıdır. Bu tezde, Dr. M. Bodur'un önerisi olan zaman boyutlu filtreleme yönteminin yüz görüntüleri üzerindeki etkisi incelenmektedir. Zamansal ortalama, medyan ve maksimum filtrelerde her pikselin parlaklığı, çevreleyen komşu piksellerin yanısıra ardışık görüntülerdeki zamansal komşu piksellerin yoğunlukları da kullanarak hesaplanır. Önerilen tekniğin görüntü üzerindeki etkisi, düşük çözünürlüklü görüntülerin piksellerini referans amaçlı kullanılan orijinal yüksek çözünürlüklü görüntünün pikselleriyle karşılaştırarak ortalama karesel hata (MSE) ve tepe sinyal gürültü oranı (PSNR) olarak elde edilmiştir. Testlerde, ortalama fıltre ile karşılaştırıldığında medyan fıltrenin daha etkin olduğu görülmüştür. Anahtar Kelimeler: Zamanda Ortalama Filtre, Zamanda Medyan Filtre, Görüntü Çözünürlüğü, Görüntü Filtre Etkinliği.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2017. Supervisor: Assoc. Prof. Dr. Mehmet Bodur.
Keywords: Computer Engineering; Image processing-Digital techniques; Temporal Mean Filter; Temporal Median Filter; Image Resolution; Effectiveness of Image Filter